Oncological outcomes of laparoscopic versus open rectal cancer resections: meta-analysis of randomized clinical trials. Issue 5 (22nd March 2021) - Creavin, B; Kelly, M E; Ryan, É J; Ryan, O K; Winter, D C
Abstract: Background: The role of laparoscopic rectal cancer surgery has been questioned owing to conflicting reports on pathological outcomes from recent RCTs. However, it is unclear whether these pathological markers and the surgical approach have an impact on oncological outcomes. This study assessed oncological outcomes of laparoscopic and open rectal cancer resections. Methods: A meta-analysis of RCTs was performed. Primary endpoints included oncological outcomes (disease-free survival (DFS), overall survival (OS), local recurrence). Secondary endpoints included surrogate markers for the quality of surgical resection. Results: Twelve RCTs including 3744 patients (2133 laparoscopic, 1611 open) were included. There was no significant difference in OS (hazard ratio (HR) 0.87, 95 per cent c.i. 0.73 to 1.04; P = 0.12; I 2 = 0 per cent) and DFS (HR 0.95, 0.81 to 1.11; P = 0.52; I 2 = 0 per cent) between laparoscopic and open rectal resections. There was no significant difference in locoregional (odds ratio (OR) 1.03, 95 per cent c.i. 0.72 to 1.48; P = 0.86; I 2 = 0 per cent) or distant (OR 0.87, 0.70 to 1.08; P = 0.20; I 2 = 7 per cent) recurrence between the groups. Achieving a successful composite score (intact mesorectal excision, clear circumferential resection margin and distal margin) was significantly associated with improved DFS (OR 0.55, 0.33 to 0.74; P < 0.001; I 2 = 0 per cent). An intact or acceptable mesorectal excision (intact mesorectal excision with or without superficial defects) had no impact on DFS. Finally, a positive CRM was associated with worse DFS. Conclusion: Well performed surgery (laparoscopic or open) achieves excellent oncological outcomes with very little difference between the two modalities. The advantage and benefit of minimally invasive surgery should be assessed on an individual basis. Abstract : Previous studies have questioned laparoscopic surgery owing to poor surrogate pathological markers. This meta-analysis of RCTs showed equivalent oncological outcomes between laparoscopic and open surgery. The use of composite scores may help stratify patients with worse disease-free survival. ongoing comparison